Effects of body position on slide boarding performance by cross-country skiers - Leirdal, S.; Saetran, L.; Roeleveld, K.; Vereijken, B.; Braten, S.; Loset, S.; Holtermann, A.; Ettema, G. (Medicine & Science in Sports & Exercise, 2006)
Purpose: In this study, we examined the effects of body position (from deep to high position) in slide boarding by well-trained cross-country skiers. The main hypothesis was that a deeper, more "crouched" position would lead to reduced air resistance and enhanced power production during explosive extension of the lower limbs, and thereby to an increased performance, even though the upper extremity may not be used for poling in this deep position.